Orthogonal pattern of spinnable multiwall carbon nanotubes for electromagnetic interference shielding effectiveness. (November 2019) - Lee, Duck Weon; Kim, Hyunsoo; Moon, Ji Hwan; Jeong, Jae-Hun; Sim, Hyeon Jun; Kim, Bum Joon; Hyeon, Jae Sang; Baughman, Ray H.; Kim, Seon Jeong
Abstract: The need for thin and lightweight electromagnetic interference shielding materials is rapidly increasing in several industries, such as aerospace and telecommunication. This research finds that a shielding material, which is developed by the orthogonal pattern of spinnable multiwall carbon nanotubes (MWNTs), is ultra-light weight, thin, and has a high shielding effectiveness (SE). An orthogonal pattern, generated by just alignment of the spinnable MWNTs without adding any support materials such as polymers, ceramics, and magnets demonstrates that it is possible to efficiently attenuate electromagnetic interference (EMI) in the X-band frequency range (8.2–12.4 GHz). EMI SE in the developed shielding material is about 19.2 dB with a specific shielding effectiveness (SSE)/t (thickness) value of 73, 633 dB cm 2 g −1 at a thickness of about 4.48 μm. In addition, absorption effectiveness in this shielding material is as high as 96.3%, which provides excellent ability to reduce the secondary damage by reflection. Graphical abstract: Image 1